STRATEGI INTERNALISASI NILAI IMAN KEPADA ALLAH DI KELAS QONUNI 3 DAN 4 DI KUTTAB AL-FATIH SIDOARJO - Muhammad Hambal Shafwan; Din muhammad zakariya; Imron Baihaqi (Program Studi Pendidikan Agama Islam, 2023)
This research was motivated by: First, the current generation is far from the values ​​of faith in Allah in every worship. Second, the lack of faith character education in schools. Third, the lack of cooperation between home and school in education. The purpose of this research: First, to find out how the concept of faith learning in Kuttab Al-Fatih Sidoarjo. Second, what is the strategy of the Kuttab teacher in internalizing the value of faith in God at Kuttab Al-Fatih Sidoarjo. Third, the supporting factors and obstacles in internalizing the value of faith in Allah. This type of research was a field research with primary data through interviews with the head of the Kuttab, teachers and the founder of the Kuttab Al-Fatih Sidoarjo. Secondary data from the literature, all data collected and analysed by qualitative methods in descriptive form. The results showed that the strategy for internalizing the value of faith in Allah in Kuttab Qonuni 3 and 4 is to motivate, adjust to the psychological conditions of students, build good cooperation between Faith teachers and Qur’an teachers, cooperate with students’ parents and pray. The supporting factors for the students were conditioned, the cooperation of the Faith teacher, the Qur'an teacher and the students' parents. The barrier factor was gadgets and students’ parents.